Forest disturbance and growth processes are reflected in the geographical distribution of large canopy gaps across the Brazilian Amazon. (19th October 2022) - Reis, Cristiano Rodrigues; Jackson, Toby D.; Gorgens, Eric Bastos; Dalagnol, Ricardo; Jucker, Tommaso; Nunes, Matheus Henrique; Ometto, Jean Pierre; Aragão, Luiz E. O. C.; Rodriguez, Luiz Carlos Estraviz; Coomes, David A.
Abstract: Canopy gaps are openings in the forest canopy resulting from branch fall and tree mortality events. The geographical distribution of large canopy gaps may reflect underlying variation in mortality and growth processes. However, a lack of data at the appropriate scale has limited our ability to study this relationship until now. We detected canopy gaps using a unique LiDAR dataset consisting of 650 transects randomly distributed across 2500 km 2 of the Brazilian Amazon. We characterized the size distribution of canopy gaps using a power law and we explore the variation in the exponent, α . We evaluated how the α varies across the Amazon, in response to disturbance by humans and natural environmental processes that influence tree mortality rates. We observed that South‐eastern forests contained a higher proportion of large gaps than North‐western, which is consistent with recent work showing greater tree mortality rates in the Southeast than the Northwest. Regions characterized by strong wind gust speeds, frequent lightning and greater water shortage also had a high proportion of large gaps, indicating that geographical variation in α is a reflection of underlying disturbance processes. Forests on fertile soils were also found to contain a high proportion of large gaps, in part because trees grow tall on these sites and create large gaps when they fall; thus, canopy gap analysis picked up differences in growth as well as mortality processes. Finally, we found that human‐modified forests had a higher proportion of large gaps than intact forests, as we would expect given that these forests have been disturbed. Synthesis . The proportion of large gaps in the forest canopy varied substantially over the Brazilian Amazon. We have shown that the trends can be explained by geographical variation in disturbance and growth. The frequency of extreme weather events is predicted to increase under climate change, and changes could lead to greater forest disturbance, which should be detectable as an increased proportion of large gaps in intact forests. Abstract : The proportion of large gaps in the forest canopy varied substantially over the Brazilian Amazon. We have shown that the trends can be explained by geographical variation in disturbance and growth. The frequency of extreme weather events is predicted to increase under climate change, and changes could lead to greater forest disturbance, which should be detectable as an increased proportion of large gaps in intact forests. Resumo: Clareiras são aberturas no dossel da floresta decorrentes da queda de galhos e de processos de mortalidade das árvores. A distribuição geográfica de grandes clareiras pode refletir uma variação desses processos de crescimento e mortalidade. Contudo, a falta de informação em escala apropriada, até o momento, tem limitado a capacidade de estudar essa relação. Nós detectamos essas clareiras utilizando um conjunto de dados LiDAR contento 650 transectos aleatoriamente distribuídos em aproximadamente 2500 km 2 de floresta na Amazônia Brasileira. Com isso, caracterizamos o tamanho e a distribuição das clareiras a partir da função power‐law e exploramos a variação no coeficiente α dessa função. Avaliamos como o α varia ao longo da Amazônia em resposta da perturbação antrópica e dos processos ambientais que ocorrem naturalmente e que influenciam a taxa de mortalidade das árvores. Foi possível observar que florestas localizadas na região Sudeste continham uma maior proporção de grandes clareiras que a região Noroeste da Amazônia, o que é consistente com um estudo recente que mostrou uma maior taxa de mortalidade seguindo o mesmo padrão. Locais caracterizados por ventos fortes, alta frequência de queda de raios e acentuado déficit hídrico apresentaram uma maior proporção de clareiras grandes, indicando que a variação geográfica em α pode ser um reflexo dos processos de perturbação subjacentes. Florestas sobre solos férteis também tendem a apresentar uma maior proporção de clareiras maiores, em parte porque as árvores crescem mais em altura nesses locais e criam clareiras maiores quando caem. Portanto, a análise de clareias capturou diferenças em crescimento e, também, em processos de mortalidade. Por fim, este estudo mostrou que florestas modificadas pelo homem tem maior proporção de clareiras maiores que as florestas intactas, como esperado para florestas onde há algum nível de perturbação antrópica. Síntese . A proporção de grandes clareiras no dossel florestal variou substancialmente ao longo da Amazônia Brasileira. Neste trabalho, mostramos que a tendência na distribuição do tamanho e frequência das clareiras pode ser explicada pela variação geográfica dos processos de perturbação e crescimento da floresta. Eventos climáticos extremos serão mais frequentes por consequência das mudanças climáticas e, tais alterações, irão acelerar processos de perturbação florestal onde será possível detectar o aumento da proporção de grandes clareiras mesmo em florestas intactas.